2016
DOI: 10.4081/monaldi.2006.579
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of quality of life after lung transplant: an Italian collaborative study

Abstract: The study identified exertional dyspnea as the main determinant of QoL as measured both by SF36 (PCS) and GHQ. Other objective measures contributed only to the PCS. Thus, the SF-36 (PCS) and GHQ were useful in identifying patients who needed treatment not only for complications but also psychological support and continued physical rehabilitation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 18 publications
0
4
0
1
Order By: Relevance
“…CF patients were found to report the best self-perceived quality of well-being. Furthermore, Ricotti and collegues confirmed these findings [5].…”
Section: Discussionmentioning
confidence: 55%
See 1 more Smart Citation
“…CF patients were found to report the best self-perceived quality of well-being. Furthermore, Ricotti and collegues confirmed these findings [5].…”
Section: Discussionmentioning
confidence: 55%
“…Various clinical studies investigated psychological problems, physical condition, diagnosis and individual characteristics for their potential to influence HRQOL and elucidated debatable values for these variables [4][5][6][7]. However, clinical and non-clinical predictors of HRQOL are still controversial.…”
Section: Introductionmentioning
confidence: 99%
“…Although the largest prospective study to date, described earlier, shows that older age did not impact improvements in HRQL at a level that exceeded the MCID, most of the literature demonstrates lower HRQL in older lung transplant recipients. 13,16,[109][110][111] Although the reasons for these discrepancies are not clear, it is possible that the system of lung allocation may be relevant. The study that found no association between age and HRQL was performed in Canada, where allocation is based on a more subjective assessment of the need for transplant instead of the LAS or time accrued on the waiting list.…”
Section: How Patient-specific Factors Impact Improvements In Hrql Aftmentioning
confidence: 99%
“…General HRQoL was measured using the internationally validated SF-36 [16][17][18][19][20]. In particular, we used the Italian version of the SF-36 (version 1.6), created by the International Quality of Life Assessment Project.…”
Section: Health-related Quality Of Life Instrumentsmentioning
confidence: 99%